2018
DOI: 10.1016/j.scitotenv.2018.03.261
|View full text |Cite
|
Sign up to set email alerts
|

High nitrogen isotope fractionation of nitrate during denitrification in four forest soils and its implications for denitrification rate estimates

Abstract: Denitrification is a major process contributing to the removal of nitrogen (N) from ecosystems, but its rate is difficult to quantify. The natural abundance of isotopes can be used to identify the occurrence of denitrification and has recently been used to quantify denitrification rates at the ecosystem level. However, the technique requires an understanding of the isotopic enrichment factor associated with denitrification, which few studies have investigated in forest soils. Here, soils collected from two tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Isotopic effects have been described ranging from 5‰ to 30‰ for pure culture (Granger et al, 2008;Mariotti et al, 1981) and 6‰ to 65‰ for natural soils Wang et al, 2018). The apparent average isotopic effect of denitrification determined with our field data was ~5‰ (Figure 4), which is at the low end of the global reported range.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Isotopic effects have been described ranging from 5‰ to 30‰ for pure culture (Granger et al, 2008;Mariotti et al, 1981) and 6‰ to 65‰ for natural soils Wang et al, 2018). The apparent average isotopic effect of denitrification determined with our field data was ~5‰ (Figure 4), which is at the low end of the global reported range.…”
Section: Discussionmentioning
confidence: 60%
“…While isotopic effects for N uptake and leaching show little variation (Evans, ; Granger et al, ), isotopic effects of denitrification itself vary over large ranges. Isotopic effects have been described ranging from 5‰ to 30‰ for pure culture (Granger et al, ; Mariotti et al, ) and 6‰ to 65‰ for natural soils (Houlton & Bai, ; Wang et al, ). The apparent average isotopic effect of denitrification determined with our field data was ~5‰ (Figure ), which is at the low end of the global reported range.…”
Section: Discussionmentioning
confidence: 99%
“…Under the anaerobic condition, the 15 ε of NO production from forest soils was significantly smaller than agriculture and grassland soils (Table 3). Previous studies reported that 15 ε was highly correlated with denitrification rates for the studied soils, with 15 ε exponentially decreasing with an increasing NO 3 − consumption rates (expressed as rate constant k 1 ) (Mariotti et al, 1988; Wang et al, 2018). Similar to these findings, across forest and grassland soils in the present study, 15 ε was also found to exponentially decrease with the denitrification rates (Figure 9).…”
Section: Discussionmentioning
confidence: 77%
“…Second, the fractionation factor for 15 N is generally on the level of part per thousand (ppt, or ‰). For instance, the fractionation factor ( 15 ε = δ 15 N A ‐ δ 15 N B ) for denitrification ranged from 5‰ to 40‰ in open ocean system (Wang et al ). However, this number is negligible compared with the δ 15 N in our work (generally ≥1000), because the 15 N compound was spiked at high levels as the incubation substrate ( 15 N: 14 N usually ≥1).…”
Section: Assessmentmentioning
confidence: 99%